Ion Channel Activities in Neural Stem Cells of the Neuroepithelium - Masayuki Yamashita (Stem Cells International)
During the embryonic development of the central nervous system, neuroepithelial cells act as neural stem cells. They undergo interkinetic nuclear movements along their apico-basal axis during the cell cycle. The neuroepithelial cell shows robust increases in the nucleoplasmic [Ca2+] in response to G protein-coupled receptor activation in S-phase, during which the nucleus is located in the basal region of the neuroepithelial cell. This response is caused by Ca2+ release from intracellular Ca2+ stores, which are comprised of the endoplasmic reticulum and the nuclear envelope. The Ca2+ release leads to the activation of Ca2+ entry from the extracellular space, which is called capacitative, or store-operated Ca2+ entry. These movements of Ca2+ are essential for DNA synthesis during S-phase. Spontaneous Ca2+ oscillations also occur synchronously across the cells. This synchronization is mediated by voltage fluctuations in the membrane potential of the nuclear envelope due to Ca2+ release and the counter movement of K+ ions; the voltage fluctuation induces alternating current (AC), which is transmitted via capacitative electrical coupling to the neighboring cells. The membrane potential across the plasma membrane is stabilized through gap junction coupling by lowering the input resistance. Thus, stored Ca2+ ions are a key player in the maintenance of the cellular activity of neuroepithelial cells.